The individual and the welfare state life histories in Europe - Börsch-Supan, Axel. 1954-; Brandt, Martina; Hank, Karsten; Schröder, Mathis; SpringerLink (Online Service). (Heidelberg, Germany Springer Berlin, 2011)
Our health, our income and our social networks at older ages are the consequence of what has happened to us over the course of our lives. The situation at age 50+ reflects our own decisions as well as many environmental factors, especially interventions by the welfare state such as education policies, access to health care and many types of social protection from poverty relief to housing subsidies and maternity support. This book explores the richness of 28,000 life histories in thirteen European countries? ranging from Scandinavia to Central and Eastern Europe to the Mediterranean? collected as part of the Survey of Health, Ageing and Retirement in Europe (SHARE). Combining these data with a comprehensive account of European welfare state interventions provides a unique opportunity to answer the important public policy questions of our time ? how the welfare state affects people's incomes, housing, families, retirement, volunteering and health. The overarching theme of the welfare state creates a book of genuinely interdisciplinary analyses, a valuable resource for economists, gerontologists, historians, political scientists, public health analysts, and sociologists alike.
Electronic reproduction.
Keywords: Welfare state -- Europe